3D reconstruction and other aspects related to historic heritage preservation Cassiano Ricardo Public Library - Silva, Lucas Cunha da; Cristofoli, Giovanna Rocha; Benini , Sandra Medina (Technical and Scientific Journal Green Cities, 2021)
This article aims to present a 3D reconstruction of the Cassiano Ricardo Public Library in different types of views, in order to contribute to future interventions in historical heritage. Considering that heritage presents itself as a collective cultural heritage that allows the connection between the past and the present, it should be noted that some cities have managed to preserve traces of the past. For the delimitation of the universe to be studied, a qualitative research was chosen, in which the procedures had a logical basis that consisted of the following steps: prior definition of the scope, known as definition of the object of study, from which it is possible to have an orientation to guide the article; the open or exploratory stage that consisted of reviewing the literature, using books, theses, dissertations, articles, etc. on the theme, in order to support the future applications of the acquired concepts, with this it is possible to outline the objectives in an assertive way; Data collection was carried out in loco; The insertion of the research object within a framework of theoretical references, concomitantly with the empirical construction, which allowed the separation and adequacy, obtaining the products of this research; As a result, a 3D digital model was presented, which allows understanding the physical aspects of the Cassiano Ricardo Public Library in order to highlight each different particularity of the heritage. KEYWORDS: Historical Heritage. Cassiano Ricardo Public Library. 3D Digital Mockup.